Blunted Diurnal Cortisol Activity in Healthy Adults with Childhood Adversity - Kuras, Yuliya I.; Assaf, Naomi; Thoma, Myriam V.; Gianferante, Danielle; Hanlin, Luke; Chen, Xuejie; Fiksdal, Alexander; Rohleder, Nicolas (Frontiers in Human Neuroscience, 2017)
Childhood adversity, such as neglect, or physical, emotional, or sexual abuse, is prevalent in the U.S. and worldwide, and connected to an elevated incidence of disease in adulthood. A pathway in this relationship might be altered hypothalamic-pituitary-adrenal (HPA) axis functioning, as a result of differential hippocampal development in early life. A blunted diurnal cortisol slope is a precursor for many disorders. While studies have focused on HPA reactivity in relation to childhood adversity, there has been markedly less research on basal HPA functioning in those with low-to-moderate adversity. Based on previous research, we hypothesized that adults with low-to-moderate childhood adversity would have altered HPA axis functioning, as evidenced by a blunted diurnal cortisol slope and altered cortisol awakening response (CAR). Healthy adults aged 18-65 (n=61 adults; 31 males and 30 females) completed the Childhood Trauma Questionnaire. Participants provided at-home saliva samples on two consecutive days at wake-up, and 30 minutes, 1 hour, 4 hours, 9 hours, and 13 hours later; samples were averaged over the two days. We found that low-to-moderate childhood adversity predicted lower morning cortisol (ß=.-34, p=.007, R2=.21), as well as a blunted cortisol slope (ß=2.97, p=.004, R2=.22), but found no association with CAR (ß=.19, p=.14, R2=.12). Overall, we found that in healthy participants, low-to-moderate adversity in childhood is associated with altered basal HPA activity in adulthood. Our findings indicate that even low levels of childhood adversity may predispose individuals to disease associated with HPA dysregulation in later life.